ORGANIZATIONAL CULTURAL BARRIERS IN ERADICATING POVERTY THROUGH e-WARONG KUBE PKH - Yuce Sariningsih; Erti Dinihayati; Uga Pratama Gunawan (SAMPURASUN, 2021)
Cultural barrier often occur on electronic mutual business group (e-Warong), as is a social assistance program as a form of synergy between the Family Hope Program (PKH) and the Mutual Business Group/Kelompok Usaha Bersama (KUBE). Beneficiaries of social assistance can also make transactions on e-Warong using a Prosperous Family Card (KKS) through Electronic Data Capture (EDC). This unique program prioritizes the achievement of social and economic goals at the group level instead of individuals profit, one group consist of 10 people who have been assessed as independent and do not receive PKH assistance anymore. The previous results showed that the management ability of e-warong was still low, and it hindered the achievement of social and economic empowerment goals. Business failures are caused because they do not have a strong incentive to do business and situation is getting worse since the Covid pandemic. The aim and purposes are to asses cultural barriers in business practice of e –Warong, 2) To describe obstacles and efforts to overcome cultural, and 3. To describe practical and theoretical implications for the development of social welfare science. This study used a qualitative method with a case study approach and the data collection method was selected according to the following stages: 1) Determining the research topic, 2) Identifying secondary barrier, and 3) Explore the data sources through journals, archives, books, etc, 4) Finding and collecting data, 5) Analyze the data, and 6) Draw conclusions. Interviews were conducted with informants of e-warong and District Social Welfare Workers (TKSK) at e-Warong Karasak Bandung. The results showed there were three dimensions of culture, namely create the idea, sense of business and business intention. These three dimensions were still low especially in realizing business ideas, basically the cultural components should complement each other in conducting business to achieve goals. These findings directed to the recommendation for the supervisor of e-Warong Anugerah Sentosa to strengthening cipta-rasa-karsa (idea, sense and intention) as the basis for e-warong KUBE PKH business.